…И слышалъ неизреченные слова, которыхъ человеку нельзя слышать (библеизмы в поэзии А. Рязанова) - Штейнер, Иван Федорович; Shtejner I. (СНУ ім. Лесі Українки, 2013)
В статье анализируется использование библеизмов в оригинальных авторских формах (зномы, версеты, вершаказы) наиболее известного за рубежом современного белорусского поэта Алеся Рязанова. Прослежива¬ется эволюция от простого использования автором евангельских мотивов до собственной трактовки некоторых основополагающих принципов христианства.The article investigates the role of biblicisms in the author’s original forms (znom, verset, vershakaz) of one of the most well-known abroad modern Belarusian poet Ales Ryazanov. Here is observed the evolution from the simple use of evangelical motives to the author’s own interpretation of some fundamental principles of Christianity.
And Heard Unspeakable Words, which it is Not Lawful for a Man (Biblicisms in Ales Ryazanov’s Poetry)
Keywords: Библия; Евангелие; апостол; Христос; поэзия; человек; магия; теология; the Bible; the Gospel; apostle; Christ; poetry; human being; magic; theology